Comparative study between digital breast tomosynthesis plus digital mammography and digital mammography alone in symptomatic women using BI-RADS score - Syeed Aalishan Fatima; Majid Jehangir; Aijaz Ahmad Ganai; Masrath Quyoom (Asian Journal of Medical Sciences, 2023)
Background: Digital mammography (DM) is the only screening modality that has been proven to reduce mortality from breast cancer through early detection. However, to reduce false positive results and improve the sensitivity of DM, we undertook a study to compare the impact of digital breast tomosynthesis (DBT) to DM in the evaluation of symptomatic women using the breast imaging reporting and data system (BIRADS) score. Aims and Objectives: The aim of the study was to compare the impact of DBT to DM in the evaluation of symptomatic women using BIRADS score. Materials and Methods: This cross-sectional study of 100 symptomatic patients in the age group of 35–85 years who underwent DM and DBT was included in the study and was analyzed using the American College of Radiology-BIRADS score. Patients with a palpable breast lump, pain, nipple discharge, skin dimpling, or skin changes over breast and nipple inversion or other nipple abnormalities were included in the study. Results: Comparison based on the diagnostic accuracy of mammography alone and mammography plus DBT based on BIRADS score revealed DM had a sensitivity of 96%, specificity of 40.6%, a positive predictive value (PPV) of 72.9% and negative predictive value (NPV) of 86.7% with an accuracy of 75.3% while DM plus DBT had a sensitivity of 98.1%, specificity of 46.9%, the PPV of 75.4%, and NPV of 78.8%. There was no significant increase in sensitivity (P=1.000), specificity (P=0.614), PPV (0.734), and accuracy (0.584). Conclusion: DM plus DBT does not change the BIRADS scoring but its addition increases the diagnostic confidence while there is no significant increase in sensitivity/specificity/PPV/NPV or diagnostic accuracy using DM plus DBT.